Analisis Semiotika John Fiske Pada Iklan Kampanye Pemilu Presiden 2019 Jokowi-Ma’ruf Amin Di Televisi - Muhammad Adela Saputra Habu Dahid (VisArt: Jurnal Seni Rupa dan Design, 2023)
Ahead of the 2019 Indonesian presidential election, presidential candidate pairs are aggressively displaying their campaign advertisements through various media. This study uses John Fiske's Codes of Television semiotic method which is divided into three levels, namely representation, reality and ideology. As well as the Nowak & Warneryd campaign model to analyze the meaning and message content of the 2019 Presidential General Election campaign advertisement for candidate pair number 01 Jokowi-Ma'ruf Amin. The results of this study indicate that this advertisement depicts Jokowi as a humble, caring leader candidate for others which can be seen from the various activities carried out with the community and also depicts a firm leader. This advertisement is a form of campaign carried out in introducing the figure of President Jokowi in the community, as well as an effort to form a positive perception to a wide audience with the aim of gaining the votes of the Indonesian people to vote for Jokowi - Ma'ruf Amin in the 2019 presidential general election contest.